Functional Outcome of Acromioclavicular joint dislocation Type III injuries treated with Hook Plate - Adhikari, Vijayendra; Sitaula, Prasamsha; Singh, Sumi; Shrestha, Praphulla; Chalise, Pralhad Kumar; Mishra, Anil Kumar; Singh, Ramesh Prasad (Nepal Medical College Journal, 2024)
The acromioclavicular joint (AC) dislocation is a complex injury due to the disruption of ligaments and joints, leading to instability and pain. Rockwood type III injuries remain controversial, so clinical evaluation should be taken into consideration before deciding the treatment modalities. The study aimed to evaluate the functional outcome of AC joint dislocation type III injuries treated with a hook plate. A total of 30 patients with AC Joint Dislocation Type III injuries were treated with open reduction and fixation with hook plate during a period of 18 months. The functional outcome was evaluated using constant murley score, the mean score of which was 82 (58-96). There were 7 (23.33%) cases of plate impingement and the symptoms was improved after plate removal. The hook plate is a good fixation device for the treatment of AC joint dislocation -Rockwood type III injuries with minimal complications, as it is a simple procedure, with good functional outcome, without ligamentous procedure and the only drawback is second surgery for implant removal.